Effect of salt stress on antioxidant enzyme activity and hydrogen peroxide content in chromosome segment substitution line of ‘Khao Dawk Mali 105’ rice - Chutimanukul, Panita; Kositsup, Boonthida; Plaimas, Kitiporn; Siangliw, Meechai; Toojinda, Theerayut (Agriculture and Natural Resources, 2019)
Chromosome segment substitution lines (CSSLs) of Thai jasmine rice ‘Khao Dawk Mali 105ʹ (KDML105) have been developed containing drought-tolerance genes from DH212. One of these CSSLs (CSSL16) showed salt tolerance in physiological responses to salt stress at the seedling and vegetative stages. This study compared the antioxidant enzyme activity and hydrogen peroxide (H2O2) content at the seedling stage of CSSL16 with those of KDML105 rice and ‘Pokkaliʹ, the standard check for salt-tolerant rice. CSSL16 had lower standard evaluation system (SES) scores under salt stress than KDML105. CSSL16, KDML105 and Pokkali under 75 mM NaCl treatment had differential responses in antioxidant enzyme activities, namely catalase (CAT), guaiacol peroxidase (GPX), superoxide dismutase (SOD), ascorbate peroxidase (APX) and glutathione reductase (GR). Pokkali had the highest CAT activity after 3 d of salt stress (DSS), whereas CSSL16 and KDML105 showed low CAT activity. Thus, CAT might not be an important enzyme in the antioxidant system of CSSL16. In the ascorbate-glutathione cycle, APX and GPX activities in CSSL16 were higher than those of KDML105 after 2 DSS, which was consistent with the lowest SES phenotype in this line. The GR activity was similar in all three rice lines. The highest H2O2 content during salt stress of KDML105 was 1.9-fold higher than that of CSSL16. These data suggested that APX and GPX may play important roles in the reactive oxygen species scavenging system in CSSL16. Based on the comparison between CSSL16 and KDML105 genomic sequence, SNPs were found in OsAPX7 and several peroxidase genes. These may contribute to the different in antioxidant enzyme activity levels and lead to the salt tolerant ability in CSSL16.